Étrangers de l'intérieur . Inside Strangers - Jourdan, Juliette (Memoire Magnetique Productions, 2008)
Verzio FF Submission In a small town in the north of the Czech Republic, the mayor had a wall built to isolate the Roma houses from the rest of the population. Backed by sympathizers from all over the country, the outraged Roma dismantled the wall. The country was divided and Maticni Street made it into the international press.